CIPPA Model Child-Centered Instruction Module: CIPPA Model - เสวกวิ, อุษาพร; ทรงกำพล, แน่งน้อย (Ratchaphruek Journal, 2019)
The objective of the research is to create and develop the Mathematics Instruction Module which use the principle of child center learning and study on the subject “Calculus for Science Student I” that offer for all first year student of Faculty of Science. Since the principal of child-centered learning will stimulate student to think and find the concept of the study by themselves which is meaningful for them. The teacher should change the function to be facilitator, supporter and knowledge expert. In this research, the researcher create the instruction module by use CIPPA Model for the content which concern with definition, rule, theory and application. While the content needed to create computational skill will be used Drill and Practice teaching model. The researcher selected 2 groups out of 10 groups to be experimental and control group. The samples were separated into 4 level of school GPA due to making both group equally likely and then an achievement of each level of both sample groups were compared by two-way ANOVA and t-test statistic, the result showed that an achievement of experimental group is significantly higher than control group at level 0.05 for 3 type of the content. Key words: child-centered learning, CIPPA model, drill and practice teaching model.